Pengaruh Kepemimpinan Transformasional Kepala Sekolah terhadap Kinerja Guru SMP Negeri di Kota Banjarbaru Dimediasi oleh Iklim Kerja dan Komitmen Kerja - Lilis Apriyanti; Ahmad Suriansyah; Sulaiman Sulaiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to describe the principal's transformational leadership, work climate, work commitment, and teacher performance and then analyze their influence directly and indirectly. The research population was 390 teachers from 14 schools, and 198 respondents were taken as research samples using a proportionate random sampling technique. Data analysis uses descriptive analysis, classical assumption testing, hypothesis testing, and path analysis. The research results show there is a direct influence of the principal's transformational leadership on the work climate; There is no direct influence of the principal's transformational leadership on work commitment; There is a direct influence of the principal's transformational leadership on teacher performance; There is a direct influence of work climate on teacher performance; There is no direct effect of work commitment on teacher performance; There is an indirect influence of the principal's transformational leadership through work climate on teacher performance; There is no indirect influence of the principal's transformational leadership through work commitment on teacher performance. In conclusion, the principal's transformational leadership influences the current era of teachers. Keywords: Principal Transformational Leadership, Teacher Performance, Work Climate, Work Commitment